Hitching wagons to stars: celebrity, metonymy, hegemony, and the case of Will Smith. Issue 1 (2nd January 2017) - King, Claire Sisco
ABSTRACT: Representations of celebrities operate as politically and culturally significant resources for the construction, regulation, and even contestation of hegemonic discourses about race and gender in the United States. Not simply meaningful or important to fans, star images may also provide resources to critics aiming to interrogate and intervene against potentially oppressive cultural norms. Forwarding an approach called metonymic criticism, this essay argues that the associative logic of metonymy plays a central role in both the articulation of celebrity personae and the operations of hegemonic discourse formations. The analysis develops by considering the case of a star whose public image has unique probative value for studying the intersecting discourses of race and gender in US culture: Will Smith.